Depression, Anxiety and stress among pregnant women during COVID-19 at Pokhara valley. - Pahari, Sirjana Pandit (2021)
Abstract: Background: Depression, anxiety and stress among pregnant women are vital issues of public health. Pregnancy is a sensitive and emotional period of a woman's life that can be affected by various psychological factors that can adversely affect her fetus and future baby. Methods: A cross-sectional study design were used for this study to assess the status of depression, anxiety and stress among 400 pregnant women during the COVID-19 pandemic at Pokhara valley, Nepal, from May 2021 to September 2021. Convenient sampling was adopted for face-to-face interviews with an interview schedule. Data entry, management, and analysis were done with SPSS Software. Research ethics was maintained. Results: About two-fifth (37.5%) of participants were aged between 25 to 30 years. Just below a third (29.3%) participants had more than six years aged husband. A significant proportion of participants belongs to the third trimester of pregnancy. Slightly more than a fifth (21.3%) of participants had depression, a third (32.5%) anxiety and only one in ten (12.7%) participants had stress. Residential area, family type, anxiety and stress level are statistically significant relationships with depression (p<0.05). Participants' stress level had statistically significant relationships with anxiety (p<0.05). There is a significant correlation between age, husband's age, age gap, stress score, anxiety score, depression score (p <0.05). There is significant difference in depression score among rural and urban participants (t value = 1.75, p value= <0.05), among primi and multigravida participants (t value = -2.6, p value= <0.05). With ANOVA, depression, anxiety, and stress among pregnant women had significant differences among occupation, husbands' education, husband's occupation, and marital satisfaction (<0.05). Conclusions: Slightly above a quarter of participants had depression, a small number of participants had anxiety and stress. Rural area, increasing age, large age gap, multigravida, housewife, secondary level education of husbands, service holder husband, poor marital satisfaction, ethnicity, insufficient economic status were associated factors with depression and anxiety. Psychosocial counselling should be conducted in health institution by focusing on rural pregnant women. Key Words: Depression, Anxiety, Stress, Pregnant Women, COVID 19, DASS-21